Simple Medical Waste Incinerator Design and Construction - Bayu Wahyudi; Muhammad Iqbal Maulana; Mohammad Rofi’i (Lembaga Pengembangan Kinerja Dosen, 2025)
Medical waste management is a major concern in protecting public health and the environment. This study aims to design and test a simple medical waste incinerator controlled by a microcontroller, intended for use in small-scale healthcare facilities. The method used was research and development (R&D), involving need analysis, system design, hardware assembly, and performance testing of the components and waste combustion effectiveness. The results indicate that the system operates stably with voltage error rates below 1% and high temperature sensor accuracy. The incinerator achieved an average combustion effectiveness of 95% across four types of disposable medical waste. The tool can operate automatically based on temperature and time settings, utilizing readily available and energy-efficient electronic components. These findings suggest that the developed incinerator is suitable as an alternative solution for medical waste treatment in clinics or health centers and has potential for further development into an environmentally friendly and sustainable incineration system.